Analisis Implementasi Undang-Undang Nomor 32 Tahun 2009 Tentang Perlindungan dan Pengelolaan Lingkungan Hidup dalam Pencegahan Pencemaran Lingkungan (Studi Kasus PT. Semen Baturaja Kabupaten Ogan Komering Ulu) - Violita Habibana Benjo; Yahnu Wiguno Sanyoto; Herni Ramayanti (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the implementation of Law Number 32 of 2009 on Environmental Protection and Management in pollution prevention at PT Semen Baturaja (Persero) Tbk in Ogan Komering Ulu Regency. The research employs a qualitative method with a case study and institutional approach. Data were collected through in-depth interviews, field observations, and documentation from nine key informants selected by purposive sampling. Data analysis used the interactive model of Miles and Huberman. Results show that PT Semen Baturaja has administratively complied with environmental regulations by possessing an Environmental Impact Assessment (AMDAL), employing bag filter technology, conducting periodic air quality monitoring, and receiving the Green PROPER award 2024–2025. However, a gap exists between administrative compliance and empirical conditions, as communities in three ring-1 sub-districts Sukajadi, Talang Jawa, and Air Gading still experience dust pollution, vibrations, and respiratory health complaints. The company's CSR programs are perceived as more socially-oriented than focused on environmental remediation. This study concludes that the success of environmental policy implementation must be measured not only by administrative compliance but also by its actual impact on community and environmental protection.